Homeowner perspectives on the implementation of the Community Homes for Opportunity (CHO) program: an ethnographic group homes study in Southwestern Ontario Canada - Cheryl Forchuk; Sebastian Gyamfi; Heba Hassan; Bryanna Lucyk; Richard Booth (BMC, 2023)
Abstract Background The global extant literature acknowledge that housing serves as a key social determinant of health. Housing interventions that involve group homes have been found to support the recovery of persons with mental illness and those with addiction issues. The current study explored the views of homeowners in relation to a supportive housing program called Community Homes for Opportunity (CHO) that modernised a provincial group home program (Homes for Special Care [HSC]) and provided recommendations for improving the program implementation in other geographical areas of Ontario. Methods We applied ethnographic qualitative techniques to purposefully recruit 36 homeowner participants from 28 group homes in Southwest Ontario, Ontario Canada. Focus group discussions were conducted at two time points, during CHO program implementation (Fall 2018, and post implementation phases (Winter 2019) respectively. Results Data analysis yielded 5 major themes. These include: (1) general impressions about the modernization process, (2) perceived social, economic and health outcomes, (3) enablers of the modernization program, (4) challenges to implementation of the modernization program, and (5) suggestions for implementation of the CHO in future. Conclusions A more effective and expanded CHO program will need the effective collaboration of all stakeholders including homeowners for successful implementation.